Lung diffusing capacity for nitric oxide in space: microgravity gas density interactions - Karlsson, Lars L.; Van Muylem, Alain; Linnarsson, Dag (Frontiers in Physiology, 2023)
Introduction: During manned space exploration lung health is threatened by toxic planetary dust and radiation. Thus, tests such as lung diffusing capacity (DL) are likely be used in planetary habitats to monitor lung health. During a DL maneuver the rate of uptake of an inspired blood-soluble gas such as nitric oxide (NO) is determined (DLNO). The aim of this study was to investigate the influence of altered gravity and reduced atmospheric pressure on the test results, since the atmospheric pressure in a habitat on the moon or on Mars is planned to be lower than on Earth. Changes of gravity are known to alter the blood filling of the lungs which in turn may modify the rate of gas uptake into the blood, and changes of atmospheric pressure may alter the speed of gas transport in the gas phase. Methods: DLNO was determined in 11 subjects on the ground and in microgravity on the International Space Station. Experiments were performed at both normal (1.0 atm absolute, ata) and reduced (0.7 ata) atmospheric pressures. Results: On the ground, DLNO did not differ between pressures, but in microgravity DLNO was increased by 9.8% (9.5) (mean [SD]) and 18.3% (15.8) at 1.0 and 0.7 ata respectively, compared to normal gravity, 1.0 ata. There was a significant interaction between pressure and gravity (p = 0.0135). Discussion: Estimates of the membrane (DmNO) and gas phase (DgNO) components of DLNO suggested that at normal gravity a reduced pressure led to opposing effects in convective and diffusive transport in the gas phase, with no net effect of pressure. In contrast, a DLNO increase with reduced pressure at microgravity is compatible with a substantial increase of DmNO partially offset by reduced DgNO, the latter being compatible with interstitial edema. In microgravity therefore, DmNO would be proportionally underestimated from DLNO. We also conclude that normal values for DL in anticipation of planetary exploration should be determined not only on the ground but also at the gravity and pressure conditions of a future planetary habitat.